2017
DOI: 10.19082/3561
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between psychological factors and maternal social support to breastfeeding process

Abstract: IntroductionChildbirth is a stressful factor that can trigger disorders such as depression in women. The various problems characteristic to the puerperal period make mothers more prone than ever to stress, anxiety and depression. The aim of this study was to determine relationship between psychological factors and social support and breastfeeding process in mothers presenting to healthcare centers in Shahrood, Iran.MethodsThe present cross-sectional study was conducted on 465 mothers with infants aged one to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 17 publications
3
21
1
1
Order By: Relevance
“…In the literature, it has been reported that successful breastfeeding depends not only on the physiological factors but also on the mother's social and psychological conditions and that mental disorders such as depression, anxiety and stress have negative effects on breastfeeding functions . In the present study, it was aimed to assess mothers’ perceived stress levels and breastfeeding attitudes in the postpartum period, and the relationship between their perceived stress and attitudes towards breastfeeding.…”
Section: Discussionmentioning
confidence: 94%
“…In the literature, it has been reported that successful breastfeeding depends not only on the physiological factors but also on the mother's social and psychological conditions and that mental disorders such as depression, anxiety and stress have negative effects on breastfeeding functions . In the present study, it was aimed to assess mothers’ perceived stress levels and breastfeeding attitudes in the postpartum period, and the relationship between their perceived stress and attitudes towards breastfeeding.…”
Section: Discussionmentioning
confidence: 94%
“…This study found that the self-perception of sureness regarding the initiation and maintenance of LME in the immediate puerperium is associated with its duration 16 , 33 . This information obtained from primiparous women residing in Cali, with no practical experience in breastfeeding, suggests that there are factors of the immediate puerperium implicated in the causality of the duration of LME.…”
Section: Discussionmentioning
confidence: 67%
“…Este estudio encontró que la autopercepción de seguridad frente al inicio y mantenimiento de la LME en el puerperio inmediato está involucrada en la duración 16 , 33 . Esta información obtenida de mujeres primíparas residentes en Cali, sin experiencia práctica en lactancia, sugiere que en la causalidad de la duración de LME están implicados factores del puerperio inmediato.…”
Section: Discussionunclassified
“…Conversely, the early cessation of breastfeeding has been shown to have a negative effect on a woman’s psychology, as it has been associated with increased anxiety and depression symptoms within 6 months after delivery [ 26 ] and appears to be an aggravating risk factor, especially for women who are mentally burdened with pathological symptoms [ 26 ]. In general, low breastfeeding rates, a shorter duration of exclusive breastfeeding, and the cessation of breastfeeding before the completion of 6 months are associated with increased anxiety and/or depression and contribute to the mother’s disappointment [ 37 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%